2020
DOI: 10.3390/cells9030572
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles from Hyperammonemic Rats Induce Neuroinflammation and Motor Incoordination in Control Rats

Abstract: Minimal hepatic encephalopathy is associated with changes in the peripheral immune system which are transferred to the brain, leading to neuroinflammation and thus to cognitive and motor impairment. Mechanisms by which changes in the immune system induce cerebral alterations remain unclear. Extracellular vesicles (EVs) seem to play a role in this process in certain pathologies. The aim of this work was to assess whether EVs play a role in the induction of neuroinflammation in cerebellum and motor incoordinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 52 publications
3
21
0
Order By: Relevance
“…Our findings confirm the production of extracellular vesicles from C6 cells and astrocytes [66,67], and represent the first demonstration that hyperammonaemia can increase extracellular vesicle production from C6 cells. This complements in vivo studies, using a dietary manipulation approach to induce chronic hyperammonaemia, that showed peripheral production of extracellular vesicles that promote neuroinflammation in astrocytes [68]. Our functional data demonstrate that hyperammonaemia-induced extracellular vesicles from C6 cells are inhibitory to CNP-stimulated cGMP accumulation in GPNT cells.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our findings confirm the production of extracellular vesicles from C6 cells and astrocytes [66,67], and represent the first demonstration that hyperammonaemia can increase extracellular vesicle production from C6 cells. This complements in vivo studies, using a dietary manipulation approach to induce chronic hyperammonaemia, that showed peripheral production of extracellular vesicles that promote neuroinflammation in astrocytes [68]. Our functional data demonstrate that hyperammonaemia-induced extracellular vesicles from C6 cells are inhibitory to CNP-stimulated cGMP accumulation in GPNT cells.…”
Section: Discussionsupporting
confidence: 76%
“…Extracellular vesicle production is associated with various metabolic, cardiovascular and endocrine pathologies [ 58 , 65 ], and their production has been demonstrated from astrocytes and C6 cells [ 66 , 67 ]. In addition, rats fed a manipulated diet to induce chronic hyperammonaemia, peripherally produce extracellular vesicles that promote neuroinflammation in astrocytes [ 68 ]. Initially, to establish whether extracellular vesicles production from C6 cells was affected by conditions of hyperammonaemia, we stimulated C6 cells in serum-free media containing 0 or 10 mM NH 4 Cl for up to 72 h, before harvesting the spent media, removing cellular debris, and centrifuging to pellet extracellular vesicles.…”
Section: Resultsmentioning
confidence: 99%
“…activation of blood cytokine receptors in endothelial cells ( Dantzer et al, 2008 ). Chronic hyperammonemia can also cause neuroinflammatory reactions ( Rodrigo et al, 2010 ; Hernández-Rabaza et al, 2016 ; Balzano et al, 2020 ) Injecting extracellular vesicles of hyperammonemic rats into the control group causes neuroinflammatory reactions and dyskinesia ( Izquierdo-Altarejos et al, 2020 ) The use of anti-TNFa therapy, which does not pass the BBB, prevents the neuroinflammatory responses induced by hyperammonemia ( Balzano et al, 2020 ). Therefore, the pro-inflammatory effect of hyperammonemia may be mediated by peripheral inflammation.…”
Section: Neuroinflammation and Immune Regulationmentioning
confidence: 99%
“…Hepatic encephalopathy is a neurological complication that results from cirrhosis and causes cognitive, psychiatric and motor impairment ( Weissenborn, 2019 ). Aberrant neuroinflammation is a common feature observed in animal models of hepatic encephalopathy ( Liu R. et al, 2020 ; Izquierdo-Altarejos et al, 2020 ). Rats subjected to bile duct ligation, a hepatic encephalopathy disease model, presented increase meningeal lymphangiogenesis that was further stimulated by increasing VEGF-C levels in the CSF ( Hsu et al, 2020 ).…”
Section: Role Of Meningeal Lymphatic (Dys)function In Neurological Disordersmentioning
confidence: 99%